Irish Bards in Shakespeare's Richard III and As You Like it - Andrew Breeze (Language, Culture, Politics)
Shakespeare alludes twice to Irish bards. In Richard III, the king mentions a prophecy by one of his imminent death; in As You Like It, Rosalind jokes on how Irish bards can supposedly rhyme rats to death. Both refer to supposed bardic powers of seeing the future and of ritual cursing of enemies. A survey of the literature shows satire and prophecy as going back to ancient times. There is in addition ample material on the (sometimes deadly) effects of satire in medieval and later Ireland, where it is known from chronicles, legal tracts, handbooks of poetry, and various surviving poems. There are in addition comic tales on how bards exploited their power, including an eleventh-century one on King Guaire's Burdensome Company, wherein the poet Senchan rhymes to death certain mice that had spoiled an egg reserved for him. Shakespeare's references can thus be related to traditions well-known in Gaul and medieval (or early modern) Ireland and Scotland.